Pengaruh Otonomi Kerja Dan Beban Kerja Terhadap Kinerja Sekretaris Desa Di Kabupaten Tanggamus - Riski Khoerul Ikhwan; Zainnur M. Rusdi; Mirwan Karim (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Performance is a very important part of an organization, where organizations generally want their members to work seriously to achieve good work results. Performance basically includes things such as mental attitudes and behavior that always hold the view that the current job must be better than the work previously done. Many factors can influence employee performance in an organization, including work autonomy and workload. This research examines the influence of work autonomy and workload on performance. Sampling in this study used a probability sampling technique with a total of 172 samples distributed among village secretaries in Tanggamus Regency. This research uses multiple linear regression analysis techniques or models with the help of SPSS 25 software. The aim of this research is to determine the effect of work autonomy and workload on the performance of village secretaries in Tanggamus Regency. The research results show that work autonomy has a positive and significant effect on performance, while workload has a negative and significant effect on performance.